Determinasi Brand Image, Kualitas Layanan dan Digital Banking Terhadap Loyalitas Nasabah Dimediasi Kepuasan Nasabah BSI KCP Malang Soetta - Asyarotul Istnaini; Fani Firmansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the influence of Brand Image, Service Quality, and Digital Banking variables on Customer Loyalty through Customer Satisfaction at BSI KCP Malang Soetta. This research uses a quantitative approach. The technique used is non-probability sampling which was taken using a purposive sampling technique. The population in this research is Bank Syariah Indonesia customers. The number of samples in this research was 200 customers. Hypothesis testing in this research uses the Smart PLS 3 test tool. The data used is the result of a questionnaire that has been distributed to BSI KCP Malang Soetta customers. The results of this research show that the brand image variable does not affect customer loyalty. The service quality variable influences customer loyalty. The digital banking variable affects customer loyalty. The customer satisfaction variable influences the customer loyalty variable. The customer satisfaction variable is not able to mediate brand image with customer loyalty. The customer satisfaction variable can mediate the service quality variable with the customer loyalty variable. The customer satisfaction variable can mediate the digital banking variable with the customer loyalty variable.